“Buscando nos encontramos”: resistir la desaparición en la Brigada Nacional de Búsqueda - Ramírez Huerta, Diana (El Colegio de México, 2025)
This article provides empirical evidence for the study of civil resistance against enforced disappearances through an analysis of the Brigada Nacional de Búsqueda (BNB), an autonomous initiative coordinated by the Red de Enlaces Nacionales (REN). By examining the strategies and objectives that have shaped its development, it is argued that this comprehensive search model –emerging in response to violence and impunity– integrates two complementary approaches: humanitarian intervention and awareness-raising against the dehumanization of victims. The main findings highlight the scope and challenges of this initiative, emphasizing the agency and expertise of social actors in contrast to the negligence of state authorities in ensuring truth, memory, and justice.